Cocrystals of the highly potent sickle cell anemia drug voxelotor with trimesic acid: a substantial enhancement in in vitro dissolution performance at physiological pH - Khan, Akram A.; Shaikh, Tabrez R.; George, Christy P.; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Global Blood Therapeutic's (GBT's) Voxelotor is an investigational oral therapy for treating sickle cell anemia. It functions by increasing the affinity between hemoglobin and oxygen, thereby preventing the sickling of red blood cells and altering the disease's pathology. The US FDA has approved Voxelotor for the treatment of sickle cell anemia and granted it an orphan drug status. However, Voxelotor is classified as a BCS class II, indicating poor water solubility. The current study explores the enhancement of Voxelotor's water solubility by forming cocrystals with trimesic acid (TMA). Novel cocrystals, cocrystal solvates, and hydrates of Voxelotor (Vox) with trimesic acid (TMA) have been developed to improve their solubility. The new solids were characterized using PXRD, DSC, TGA, XPS, HSM, and single-crystal X-ray diffraction studies, and the intermolecular interactions were quantified using Hirshfeld surface analysis. Detailed crystallographic analysis revealed strong O-H center dot center dot center dot N hydrogen bonding interactions between Vox and TMA, primarily involving the COOH functional group of TMA and the pyridine or pyrazole groups of Vox. Additionally, TMA molecules participate in further hydrogen bonding-either with themselves or with solvates, including hydrates, through mono- or dimeric O-H center dot center dot center dot O H-bonding synthons. In vitro solubility studies demonstrated a significant increase in the solubility of Voxelotor in the Vox-TMA cocrystals compared to the pristine drug at physicochemical pH 4.5 and 6.8. Stability studies confirmed that the nonsolvated multicomponent crystal retains their structural integrity under nonambient conditions without undergoing polymorphic phase transitions. In contrast, the solvated crystals, including hydrates, undergo phase transitions within the temperature range of 100-130 degrees C, losing solvents and converting into one of the nonsolvated cocrystal forms. These findings suggest that the novel Vox-TMA cocrystals have the potential to enhance the therapeutic performance and clinical utility of Voxelotor.